Physical and Chemical Characteristics of Goat Milk Powder With Different Drying Methods After Storage - Heni Rizqiati; Nurwantoro Nurwantoro; Siti Susanti; Claradhita Ayu Shauma; Andi Febrisiantosa; Triana Setyawardani (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2021)
Processing kefir into powder form is an effort to extend shelf life, prevent contamination from unwanted bacteria, and facilitate storage. For this reason, a proper drying method is needed to produce a good quality kefir powder. There are three types of drying methods used in this study, namely drying with a cabinet dryer, freeze dryer, and spray dryer. The purpose of this study was to determine the effect of different types of drying methods on pH value, solubility, viscosity, total acid, and alcohol content of goat's milk kefir powder after storage for two months. This study used a completely randomized design method with different types of drying methods, namely T1 (cabinet dryer), T2 (freeze dryer), and T3 (spray dryer). The data were analyzed using Analysis of Variance (ANOVA) with a confidence level of 95% and if it had a significant effect, it was continued with the Duncan Multiple Range Test. The results showed that the different drying methods did not show any significant effect (p > 0.05) on the pH value, solubility, viscosity, total acid, and alcohol content, so it could be concluded that the three types of drying methods did not affect physical and chemical quality of kefir powder that has been stored for two months.